Aplikasi Hermeneutika Nashr Hāmid Abū Zaid Terhadap Hadis Nabi (Studi Pada Hadis “Perintah Memerangi Manusia Sampai mereka Mengucapkan tiada tuhan selain Allah”) - Mohamad Nuryansah (Millati: Journal of Islamic Studies and Humanities, 2016)
This paper aims to understand the meaning of jihad in the present context by re-reading the hadith about “the command to fight against human until they say there is no god but Allah." The re-reading to this hadith need to do continuously, because in present context, there are a lot of violences on behalf of religious texts both derived from Qur'an and hadith. Theory used to understand the hadith is hermeneutical theory by Nasr Hamid Abu Zaid. The hermeneutic of Nasr Hamid Abu Zaid consists of three main pillars, namely finding the dalalah (meaning), magza (significance) and maskut anhu (unspoken dimensions) of the text. Based on the application of the hermeneutic, it is obtained the results that dalalah of jihad implied in Hadith is that jihad in peace way is more emphasized; while magza (significance) of the hadith is instructing that Jihad in Islamic view is only in decent way and maskut anhu (unspoken dimensions) of the Hadith is that violent jihad is prohibited.